2017
DOI: 10.1007/s10862-017-9629-3
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the Strength of the Relation Between Social Support and Post-Trauma Psychopathology

Abstract: Potentially traumatic events (PTEs) increase risk for psychopathology, including posttraumatic stress disorder (PTSD), major depressive disorder (MDD), and generalized anxiety disorder (GAD). Social support (SS) is associated with reduced symptoms for each disorder. Each disorder, however, is highly heterogeneous such that they are comprised of clusters of different symptoms. It is unclear if SS is associated with all clusters equally. The current study examined the relation between SS and the symptom clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
2
11
0
Order By: Relevance
“…As hypothesized, the symptoms of cluster B (intrusions) and cluster C (avoidance) formed a community, which represents the fear-specific symptoms of the disorder. Factor analytic work has shown that these clusters are more strongly related to each other than the other clusters of PTSD (Elhai et al, 2015;Price et al, 2017;Price and van Stolk-Cooke, 2015). Work using fear conditioning paradigms has shown that intrusions and avoidance symptoms are more strongly associated with the extinction of fear (Norrholm et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As hypothesized, the symptoms of cluster B (intrusions) and cluster C (avoidance) formed a community, which represents the fear-specific symptoms of the disorder. Factor analytic work has shown that these clusters are more strongly related to each other than the other clusters of PTSD (Elhai et al, 2015;Price et al, 2017;Price and van Stolk-Cooke, 2015). Work using fear conditioning paradigms has shown that intrusions and avoidance symptoms are more strongly associated with the extinction of fear (Norrholm et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…PTSD is comprised of four clusters, each of which has specificity from GAD and depression, however. Intrusion (Cluster-B) and avoidance (Cluster-C) consistently have weaker relations to symptoms of depression and GAD than Negative Alterations in Cognitions and Mood (NACM, Cluster-D) and Alterations to Arousal and Reactivity (Cluster-E) (Price et al, 2017;Price and van Stolk-Cooke, 2015;Watson, 2009). The quadripartite model and empirical investigations of comorbidity have been examined primarily through factor analysis (Contractor et al, 2015;Grant et al, 2008;Price and van Stolk-Cooke, 2015).…”
mentioning
confidence: 99%
“…Moreover, some studies have found that individual differences have an impact on negative psychological consequences of COVID-19 pandemic, as in the case of perceived social support ( Cao et al, 2020 ; Tull et al, 2020 ; Xiao et al, 2020 ) and emotion regulation strategies ( El Keshky et al, 2020 ; Xu et al, 2020 ). However, such variables have been less extensively studied in relation to the COVID-19 situation, despite evidence showing their protective role for mental health (e.g., Aldao et al, 2010 ; Prati and Pietrantoni, 2010 ; Aldao, Gee, De Los Reyes, and Seager, 2016 ; Kent de Grey et al, 2018 ; Price et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adequate social support positively affects psychological health and sleep function ( Prati and Pietrantoni, 2010 ; Kent de Grey et al, 2018 ). In addition, adequate social support is associated with reduced symptoms of post-traumatic stress disorder (PTSD), major depressive disorder, and generalized anxiety disorder ( Price et al, 2018 ). Moreover, a meta-analysis identified social support as the strongest protective factor for the onset of PTSD after traumatic events ( Ozer et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the conservation of resources (CORs) theory states that social support serves as an external supplement of resources that people can rely on to avoid psychological distress in stressful circumstances (Hobfoll et al, 2016 ). Perceived social support is reported to be associated with reduced symptoms from a series of mental disorders, such as major depressive disorder (MDD), posttraumatic stress disorder (PTSD), and generalized anxiety disorder (GAD), after stressful events (Price et al, 2018 ). During the COVID-19 pandemic, social support from family could have potentially alleviated depression symptoms due to the social lockdown condition (Mariani et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%